Gestational Trophoblastic Neoplasia—A Retrospective Analysis of Patients Treated at a Tertiary Care Oncology Center in North India - Gupta, Anuj; Kapoor, Akhil; Mishra, Bal Krishna; Kashyap, Lakhan; Choudhary, Amit; Singh, Arpita; Singh, Neha; Sansar, Bipinesh (South Asian Journal of Cancer, 2023)
Objectives The aim of this study was to do a retrospective analysis of patients of gestational trophoblastic neoplasia (GTN) treated at our center concerning their clinical features and treatment outcomes.Materials and Methods Patients diagnosed and treated from May 2018 to December 2021 were included. All relevant information pertaining to eligible patients was retrieved from the electronic medical records. Patients were risk-stratified based on the World Health Organization (WHO) risk scoring system with a score of seven and above being classified into the high-risk category. Patients were monitored for response by measuring β-human chorionic gonadotrophin (β-HCG) levels before each consecutive cycle.Statistical Analysis Appropriate statistical analysis was performed using SPSS version 26.Results Records of 39 eligible patients were analyzed for clinical features out of which 38 were eligible for response assessment. The median age of presentation was 28 years with the majority of patients (79.4%) diagnosed based on β-HCG levels and clinical history alone. The most common symptom was bleeding per vagina (64%), while the majority of antecedent pregnancies were abortions (59%).Of the 14 low-risk category patients, 12 received single-agent methotrexate/actinomycin D, while 2 received etoposide, methotrexate actinomycin D (EMACO) regimen. Overall response rates were 85.7% with the others responding to the second-line EMACO regimen. Five patients in this group had a WHO score of 5 or 6 and all of them responded to single-agent treatment. Among the 25 high-risk category patients, all received the EMACO regimen with high-dose methotrexate added to those with brain metastasis. The response rate was 87.5% with all the nonresponders having features of ultra-high risk of liver/brain metastasis and/or a WHO score of more than 12. While one nonresponder had expired despite treatment, the other two responded to the etoposide methotrexate and actinomycin D/ etoposide and cisplatin regimen.Conclusion Our results are in consonance with other reported studies. The subcategories of low-risk GTN with a WHO score of 5 and 6 and high-risk GTN with ultra-high-risk features deserve further research in the form of multicenter prospective studies.
Keywords: β-HCG; choriocarcinoma; gestational trophoblastic neoplasia; methotrexate; WHO score